2010
DOI: 10.1017/s0025315410000354
|View full text |Cite
|
Sign up to set email alerts
|

Studies on reproductive biology and ecology of blue swimming crabPortunus pelagicusfrom Chilika Lagoon, Orissa, India

Abstract: Portunus pelagicus a commercially important crab species found in Chilika lagoon constitutes about 20% of the total crab production. The carapace width (CW) ranges from 4.5–10.5 cm in both the sexes during the study period. The maximum abundance of male was at 6.6 to 7.5 cm CW whereas the females predominate from 6.6 to 9.5 cm CW. The relationship between carapace length (CL) and CW is linear in both sexes which indicates isometric growth. However, the relationship between CL, CW with total body weight (TW) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Earlier studies have shown intraspecific, and interspecific variation in the reproductive biology characteristics of P. pelagicus explained by, areaspecific and regional differences; e.g. in Malaysia (Ikhwanuddin et al 2009, Ikhwanuddin et al 2012, in India waters (Sahoo et al 2011), and in Philippines (Ingles and Bkaum 1989). Brachyuran crabs are categorized as iteroparous species, which have considerable variation in reproduction patterns (Hines 1982, Hines 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown intraspecific, and interspecific variation in the reproductive biology characteristics of P. pelagicus explained by, areaspecific and regional differences; e.g. in Malaysia (Ikhwanuddin et al 2009, Ikhwanuddin et al 2012, in India waters (Sahoo et al 2011), and in Philippines (Ingles and Bkaum 1989). Brachyuran crabs are categorized as iteroparous species, which have considerable variation in reproduction patterns (Hines 1982, Hines 1989).…”
Section: Introductionmentioning
confidence: 99%
“…al., 2014;Ikhwanuddin et al, 2012). This species is one of the economical valuable fisheries important commodity because of the high demand and availability jobs created for the fishermen (Lai et al, 2010;Sahoo et al, 2011;Anand and Soundarapandian, 2011;Johnston et al, 2011). According to Kembaren et al, (2012) the production of blue swimming crab in Indonesia occupied third place after China and the Philippines, with a production value of 16.4% or 28,000 tones from the rest of the world's production.…”
Section: Introductionmentioning
confidence: 99%
“…Sci., 18/3, 2017, 424-432 425 The reproductive biology of crustaceans has been widely studied, mainly of those species that have commercial value or ecological potential. Studies on the reproductive biology of Portunu's species have been carried out in various regions: in Australia (Potter et al, 1983;Sumpton 2001;de Lestang et al, 2003;Kumar et al, 2003;Johnson et al, 2010); in India (Pillay & Nair, 1971;Sahoo et al, 2011;Soundarapandian et al, 2013); in the Philippines (Batoy et al, 1987); in Malaysia (Arshad et al, 2006;Ikhwanuddin et al, 2011;Ikhwanuddin et al, 2012); in Iran (Kamrani et al, 2010;Safaie et al, 2013b;Hosseini et al, 2012;Hosseini et al, 2014 b); in Indonesia (Sara et al, 2016;Hamid et al, 2016). In Turkey, however, no research has been conducted on the reproductive biology of Lesepsian Portunus species.…”
Section: Introductionmentioning
confidence: 99%